Farmers' perception and objective validation of the impact of climate change on farming activities in Northeast Thailand. Issue 1 (1st April 2022) - Nodera, Miki; Khoiru Zaki, Muhamad; Srisutham, Mallika; Yoshida, Koshi; Noda, Keigo
Abstract: In general, there is a gap between people's subjective and objective assessment of risk and resilience and objective resilience is larger than a subjective one. The aim of this paper is to analyze farmers' perception of climate change comparing with objective data. We conducted the questionnaire survey in Khon Kaen Province in Northeast Thailand and clarified the farmers' profile, agricultural management, and perception of climate change. In addition, comparing to questionnaire result and objective data, we discussed how much the actual farmers' perception of climate change is different from the objective data. As a result, the farmers perceptions to the rainfall amount in 10 years and trend of objective data were not consistent. This gap suggests that farmers perceived changes in short-term rainfall as climate change rather than changes in long-term rainfall, and that farmers may perceive their production as decreasing due to the increased amount lost due to the expansion of paddy fields into unsuitable areas.